Opportunities and gaps in conservation incentive programs on California agricultural land - Lenhardt, Julia; Egoh, B. N. (Frontiers in Sustainable Food Systems, 2023)
There are many financial incentive programs that promote ecosystem health and biodiversity on California working lands and encourage a multitude of conservation goals. Ecosystem services are the benefits provided by nature to people, and while interest in ecosystem services has grown in recent decades, there has not yet been a review of California agricultural incentive programs through the lens of ecosystem services, despite the utility of ecosystem services to identify tradeoffs between conservation management options. Here, we analyze the documented goals and top-funded conservation practices to determine the ecosystem service priorities on California working lands. We then determine the relative impact of each of the top-funded federal conservation practices on ecosystem services. We find that there is a gap between California’s ecosystem services goals and the ecosystem services that are impacted by federal programs, and that the top funded practices are not necessarily the ones that deliver the best benefits in terms of ecosystem services. This study highlights the gaps between conservation goals and outcomes on California agricultural land, as well as the need for regional conservation monitoring to determine the impacts of incentive programs.